The diaphonic aspect of phonotactics - Bańczerowski, Jerzy (Lingua Posnaniensis, 2014)
The diaphonic aspect of phonotactics as a necessary counterpart of the isophonic aspect is being subjected to investigation. A ll assumptions and definitions are exemplified with P olish language material. Having recollected and relatively precisely explained phonological terms, indispensible for the subsequent inquiry, the distinction between diacrisis and diaphony is discussed, and several useful concepts such as the diaphonotacteme, diaphonic pair, diaphonic range, diaphonotactemic length etc. are introduced. N ext some fundamental phonotactological terms are defined to which, among others, the following belong: diaphonic load, diacritic range, the diatactophoneme, diaphonic dispersion, diacritic dispersion, types of diaphony and diacrisis. A lso some problems of diaphonic paradigm and diaphonic coding are considered. Finally, a phonotactological typology within the framework of comparative phnotactology of languages is postulated